Component analysis and antifungal activity of three Chinese herbal essential oils and their application of postharvest preservation of peach fruit. (November 2021) - Mou, Linyun; Du, Xiaolong; Lu, Xiaofei; Lu, Ya; Li, Ganpeng; Li, Jianlong
Abstract: The melting fleshed peach is highly susceptible to infection by pathogenic fungi after harvested. Although synthetic preservatives could effectively reduce the spoilage, they normally will pose a threat to the environment and human health. The essential oils (EOs) was extracted from the three Chinese herbal medicines which were considered as a better natural substitute in the application of antifungal substance. Their chemical composition was analyzed by gas chromatography-mass spectrometry (GC-MS), and principal component analysis (PCA) was used to identify possible relationships between EOs composition and habitats. In vitro test, the significantly ( P < 0.05) antifungal activity of these EOs against 6 pathogens was proved at 50 μg/mL dosing concentration. Compound preparation of EOs (CP EOs) significantly ( P < 0.001) reduced the decay index based on the optimized composition of three Chinese herbal medicine EOs through response surface methodology (RSM). CP EOs microemulsion (M-CP EOs) was developed to improve the bioavailability, which could significantly (P < 0.05) increase the antifungal activity compared with CP EOs. Consequently, these EOs could be considered for the production of natural preservative which reduced our dependence on the synthetic preservatives. Highlights: Relationships between essential oils composition and habitats was investigated. The optimum concentration of compound preparation of essential oils was optimized. Essential oil microemulsion was developed which has better antifungal activity. The essential oils could be consider as a substitute for synthetic preservatives.